Evoked potentials and abstract thinking - Tatalović Vorkapić, Sanja (Array, 2008)
Summary: The aim of this study was to investigate the relationship between measures (latency and amplitude) of evoked potentials (N1, P2, N2, P3 and SW) elicited by a standard visual oddball paradigm, and abstract reasoning measured by the Abstract Reasoning Test (TAM; Kulenović, 2003). Even though the results of most studies of evoked potentials and intelligence have been inconsistent, and although they were mostly concerned with the relationship between P300 and intelligence, it was hypothesized that participants with higher reasoning ability would show significantly shorter latencies of N1, P2 and P3 waves. Because of previously established effects of the experimental task complexity on the relationship between EP amplitude and intelligence, it was not expected for this correlation to be significant, as a very simple standard visual oddball task was used. The sample consisted of 43 participants, all female, right-handed, in the age range of 19-23 years. The evoked potentials were recorded in two trials for each participant. Active electrodes were placed on O1, O2, P3 and P4 (according to the 10-20 system), and referred to Fz. Significant negative correlation was found only between N1-wave measured on the O1 electrode and scores on the first subtest of TAM. A shorter N1-latency evoked by a visual oddball task in participants with a higher level of abstract reasoning was expected. This finding is discussed in view of psychological-functional role of the N1-wave, information processing demands of specific tasks, perceptive characteristics, and the task complexity level